Rubber Adhesion and Friction: Role of Surface Energy and Contamination Films - Tiwari, A.; Tolpekina, T.; Benthem, Hans van; Gunnewiek, M. K.; Persson, B. N. J. (Frontiers in Mechanical Engineering, 2021)
We study the influence of the surface energy and contamination films on rubber adhesion and sliding friction. We find that there is a transfer of molecules from the rubber to the substrate which reduces the work of adhesion and makes the rubber friction insensitive to the substrate surface energy. We show that there is no simple relation between adhesion and friction: adhesion is due to (vertical) detachment processes at the edge of the contact regions (opening crack propagation), while friction in many cases is determined mainly by (tangential) stick-slip instabilities of nanosized regions, within the whole sliding contact. Thus while the pull-off force in fluids may be strongly reduced (due to a reduction of the work of adhesion), the sliding friction may be only slightly affected as the area of real contact may be dry, and the frictional shear stress in the contact area nearly unaffected by the fluid.